What we don't talk about in health inequalities: Value judgements - John Ford; Michelle Black; Jo Morling (Public Health in Practice, 2023)
Hundreds of pages of journals are filled every year describing health inequalities, but few discuss why these differences are unfair and avoidable. These value judgements raise important philosophical and ethical questions.
Keywords: Public Health; Value Judgement; Health inequalities